2018
DOI: 10.1111/eea.12701
|View full text |Cite
|
Sign up to set email alerts
|

Mate‐searching behavior in the invasive German wasp, Vespula germanica, in Patagonia

Abstract: In order to increase the probability of reproduction, social insects can adopt various mate‐finding strategies, such as increasing densities of males at specific locations, and/or visual and chemical cues that attract the opposite sex. In field and laboratory studies we investigated strategies used by the invasive eusocial wasp Vespula germanica (Fabricius) (Hymenoptera: Vespidae). In tethered flight assays, we established contrasting flight patterns in females and males that may partly explain how related ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Although these can be relatively large molecules with low volatilities, some of them can be perceived without tactile interaction at short distances, as established through behavioral studies on ants of the www.nature.com/scientificreports www.nature.com/scientificreports/ genus Camponotus and bumblebees, who can discriminate related from unrelated individuals from a short distance [34][35][36] . Having mentioned this, the relevance of visual cues in kin recognition cannot be ruled out, since their role in this aspect has been investigated and they can be important in sexual selection, mate attraction and mate choice 8,31,33,37 . For example, females of Polistes simillimus may evaluate male facial coloration during the choice of a sexual partner 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these can be relatively large molecules with low volatilities, some of them can be perceived without tactile interaction at short distances, as established through behavioral studies on ants of the www.nature.com/scientificreports www.nature.com/scientificreports/ genus Camponotus and bumblebees, who can discriminate related from unrelated individuals from a short distance [34][35][36] . Having mentioned this, the relevance of visual cues in kin recognition cannot be ruled out, since their role in this aspect has been investigated and they can be important in sexual selection, mate attraction and mate choice 8,31,33,37 . For example, females of Polistes simillimus may evaluate male facial coloration during the choice of a sexual partner 38 .…”
Section: Discussionmentioning
confidence: 99%
“…With gynes not having a selective behavior toward potential mates, a mechanism to increase outbreeding, regulated by drones, would make sense. It has been recently suggested that dispersal in V. germanica is gyne-biased, while gynes have the potential of flying relatively large distances, drones fly relatively little, which implies remaining in the vicinity of the parental nest, where kin density is high 8,39 . This would suggest that, if no additional mechanism for increasing aggregation heterogeneity was in place, the risk of drone aggregations being conformed by a relatively high proportion of nestmates, would be high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in haplodiploid hymenopterans, due to their particular mechanism of sex determination (i.e., single-locus complementary sex-determination system), the costs of inbreeding can be even higher, because sterile diploid males develop and reach the adult stage, representing an extra cost for the colony (Van Wilgenburg et al ., 2006; Tabadkani et al ., 2012). Many hymenopteran species display behaviours that reduce inbred matings, such as mating with more than one male (polyandry), kin recognition and differential spatial and temporal distribution patterns between sexes (Mazzi et al ., 2011; Loyau et al ., 2012; Pizzari and Wedell, 2013; Vitikainen et al ., 2015; Martinez et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies on reproductive behaviour in V. germanica indicate that mating occurs during the end of autumn, with field observations suggesting that drones emerge ahead of gynes and congregate in specific areas waiting for females to arrive (Spradbery, 1973; Post 1980; Greene, 1991). Gynes can mate more than once (polyandry), with pheromones and visual cues suggested to be involved in mate location (Ross, 1983; Reed and Landolt, 1990; Ayasse et al ., 2001; Goodisman et al ., 2002; Brown et al ., 2013; Loope et al ., 2014; Derstine et al ., 2017; Martinez et al ., 2018). Also, tethered flight bioassays indicate that movement is greater in pre-hibernated gynes than in drones, thus favouring spatial separation (Masciocchi et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%